Anthropometric studies of patients with nonalcoholic fatty liver disease - K. V. Pivtorak (Zaporožskij Medicinskij Žurnal)
There is a great interest in non-invasive markers of non-alcoholic fatty liver disease (NAFLD) in clinical practice because liver biopsy is performed only for certain indications.